2020
DOI: 10.1016/j.celrep.2020.108054
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Dorsolateral Habenula Is Required for Updating Learned Behaviors

Abstract: Summary Operant learning requires multiple cognitive processes, such as learning, prediction of potential outcomes, and decision-making. It is less clear how interactions of these processes lead to the behavioral adaptations that allow animals to cope with a changing environment. We show that juvenile zebrafish can perform conditioned place avoidance learning, with improving performance across development. Ablation of the dorsolateral habenula (dlHb), a brain region involved in associative learning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 89 publications
2
50
0
Order By: Relevance
“…Moreover, registration of transgenic and experimental brains on standardized atlases (Kunst et al, 2019; Randlett et al, 2015; Tabor et al, 2019) enables scientists to identify neuronal populations involved in specific behaviors (Haesemeyer, Robson, Li, Schier, & Engert, 2018; Randlett et al, 2015; Wee et al, 2019) or diseases (Thyme et al, 2019) in an unbiased manner. Beside investigations at larval stages, recent studies at juvenile zebrafish (2–5 weeks) showed that this relatively transparent (Fore, Cosacak, Verdugo, Kizil, & Yaksi, 2019) development stage allows non‐invasive imaging (Jetti, Vendrell‐Llopis, & Yaksi, 2014; Vendrell‐Llopis & Yaksi, 2015) and exhibit cognitively demanding behaviors such as learning (Palumbo, Serneels, Pelgrims, & Yaksi, 2019; Valente, Huang, Portugues, & Engert, 2012; Yashina, Tejero‐Cantero, Herz, & Baier, 2019) and social interactions (Dreosti, Lopes, Kampff, & Wilson, 2015; Hinz & de Polavieja, 2017; Larsch & Baier, 2018; Tunbak, Vazquez‐Prada, Ryan, Kampff, & Dreosti, 2020). Altogether, we are certain that applying the wide range of methodologies described above to measure and interfere with astroglia activity will reveal exciting findings on the mechanisms and dynamics underlying neuro‐glia interactions in the context of complex behaviors and brain diseases.…”
Section: Open Questions and Opportunitiesmentioning
confidence: 99%
“…Moreover, registration of transgenic and experimental brains on standardized atlases (Kunst et al, 2019; Randlett et al, 2015; Tabor et al, 2019) enables scientists to identify neuronal populations involved in specific behaviors (Haesemeyer, Robson, Li, Schier, & Engert, 2018; Randlett et al, 2015; Wee et al, 2019) or diseases (Thyme et al, 2019) in an unbiased manner. Beside investigations at larval stages, recent studies at juvenile zebrafish (2–5 weeks) showed that this relatively transparent (Fore, Cosacak, Verdugo, Kizil, & Yaksi, 2019) development stage allows non‐invasive imaging (Jetti, Vendrell‐Llopis, & Yaksi, 2014; Vendrell‐Llopis & Yaksi, 2015) and exhibit cognitively demanding behaviors such as learning (Palumbo, Serneels, Pelgrims, & Yaksi, 2019; Valente, Huang, Portugues, & Engert, 2012; Yashina, Tejero‐Cantero, Herz, & Baier, 2019) and social interactions (Dreosti, Lopes, Kampff, & Wilson, 2015; Hinz & de Polavieja, 2017; Larsch & Baier, 2018; Tunbak, Vazquez‐Prada, Ryan, Kampff, & Dreosti, 2020). Altogether, we are certain that applying the wide range of methodologies described above to measure and interfere with astroglia activity will reveal exciting findings on the mechanisms and dynamics underlying neuro‐glia interactions in the context of complex behaviors and brain diseases.…”
Section: Open Questions and Opportunitiesmentioning
confidence: 99%
“…We observed that concomitant with brain volume expansion from 4 to 14 dpf ( Figure 1A1,A2), more cilia appeared on the dorsal telencephalon anterior to the forebrain choroid plexus (ChP) ( Figure 1B,C). At 28-32dpf, when major cognitive, learning, and social skills are acquired [43][44][45][46][47][48][49], we found that ciliated cells on the dorsal telencephalon increased not only in number, but also started to harbor brushes of cilia reminiscent of MCCs ( Figure 1A3,D1,D2). At this stage, MCCs were present on the dorsal telencephalon ( Figure 1D2) and in the forebrain ChP ( Figure 1D4), and co-existed with monociliated cells (arrows versus arrowheads).…”
Section: Motile Ciliated Cell Abundance and Onset Of Multiciliation Cmentioning
confidence: 99%
“…Before describing all the steps of our behavioral experiments in detail we want to emphasize the importance of proper and reproducible zebrafish husbandry to ensure reproducibility of most behavioral assays, including our conditioned place avoidance learning assay ( Palumbo et al., 2020 ) described in the following section.…”
Section: Before You Beginmentioning
confidence: 99%
“…Our goal is to promote standardization of animal handling procedures and setup conditions to improve animal welfare and reproducibility while studying operant learning behaviors in juvenile zebrafish. For complete details on the use and execution of this protocol, please refer to Palumbo et al. (2020) .…”
mentioning
confidence: 99%
See 1 more Smart Citation